CARACTERIZAÇÃO E CLASSIFICAÇÃO DA PRÓPOLIS PRODUZIDA NO PARANÁ ATRAVÉS DE MÉTODOS ESPECTROSCÓPICOS E CROMATOGRÁFICOS E FERRAMENTAS QUIMIOMÉTRICAS - Finger, Daiane (2014)
This study aimed to compare and classify propolis produced in Paraná-PR and also to investigate the relationship between the chemical composition of different types of propolis and the local of production. Forty-four propolis samples were provided by beekeepers from different regions of Paraná. Ethanolic extracts were used for HPLC-DAD, ESI-MS/MS, 1H NMR analyses and for cytotoxic tests in human tumor cells. The mineral content was assessed in raw propolis by GF-AAS and FAAS. Principal component analysis (PCA) was separately applied to all data set. Through ESI-MS/MS, 25 compounds were identified. Each technique provided additional information regarding the characteristics of the propolis samples from Paraná. As a result, the propolis samples were assembled into 3 groups whose classification was closely connected to the geographical origin of the samples. Group I has in its composition mainly nonpolar compounds, as cupressic, isocupressic, agathic and agathalic acids. This group includes samples from metropolitan and eastern regions and some samples from the south-central and southeastern regions. Group II comprises samples from Parana which are rich in prenylated phenolic acids derivatives from cinnamic acid, such as 3,4-dihydroxy-5-prenyl cinnamic acid, Artepillin C, dicaffeoylquinic acids, among others. The propolis samples from the north regions of Paraná (north central, northern and western pioneer center) were congregated in group II. The samples from the south-central, southeast, southwest (group III) had intermediate characteristics between groups I and II. Regarding the inorganic composition of propolis, the minerals Na, Al, Mg and Ca had the highest average values being 0.58, 0.68, 1.27 and 1.66 mg g?¹, respectively. The metal trace elements Cd, Cr and Pb were found in some propolis samples but in amounts which do not represent a potential threat to consumers` health. Regarding cytotoxicity tests, the majority of samples regardless of the collection site or chemical composition, showed cytotoxic activity against at least one cell line. It was noted that this activity did not correlate with the geographical origin of the samples. Finally, it can be concluded that principal component analysis is a useful tool to classify propolis when complex, multivariate data or large number of samples are analyzed. The analytical methodology showed in this study could be extended to assign or prove the geographical origin of propolis samples, as well as, its likely plant source.